A narrative review of the survival of dental implants placed simultaneously with lateral sinus floor elevations without the use of graft materials. (9th August 2020) - Kenyon, P.; West, N.; Claydon, N.
Abstract: This review aims to critically appraise the available evidence for the survival of implants placed simultaneously with sinus floor elevation without the use of grafting materials. The atrophic maxillary sinus may be restored with implants using a variety methods and adjunctive grafting techniques. The placement of implants in the atrophic maxillary sinus with and without bone grafting was reviewed in a systematic manner by considering the evidence presented in clinical studies. The initial search yielded 983 titles. Following title‐based, abstract‐based and full‐text evaluation 12 studies were identified, reporting on 1353 implants. Analysis identified a 98.38% survival rate at the point of uncovering. A further 0.3% of remaining implants were lost after 12 months and another 0.01% after 24 months. Beyond this point there were no further reported implant failures. Data were comparable for both grafted and ungrafted sinuses, with implants in ungrafted sinuses appearing to have a marginally higher success rate (98.11% vs. 97.87%).This review of implant data studies confirms that placing dental implants into maxillary sinuses with a graftless approach yields comparable implant survival to those cases that are grafted. This suggests that there is scope to simplify treatment protocols, decrease the risk of infection while maintaining treatment success and increase patient acceptance of sinus lift procedures.